Genotypic Differences for Nitrogen Use Efficiency and Grain Protein Deviation in Hard Winter Wheat. (1st November 2016) - Latshaw, Susan P.; Vigil, Merle F.; Haley, Scott D.
Abstract : Breeding superior bread wheat ( Triticum aestivum L.) genotypes requires sufficient genetic variation to obtain high grain yield and adequate grain protein concentration. This study was conducted to determine variation for nitrogen use efficiency (NUE) and grain protein deviation among 20 hard winter wheat genotypes in one season and for two recently released cultivars (Snowmass and Byrd) in a second season, under five N application rates (0, 28, 56, 84, 112 kg ha −1 ). Among these genotypes, the proportionate contributions of component traits to total variance for NUE ranged widely: N uptake efficiency (57–89 kg kg −1 ) and N utilization efficiency (11–43 kg kg −1 ). Across all genotypes, N utilization efficiency contributed the most to variance for NUE under moderate to high N supply while N uptake efficiency contributed more under N limiting conditions. Increased NUE promotes high grain yields, but may result in decreased grain protein concentration through the commonly observed negative correlation of these traits. Analysis of residuals from regression of grain protein concentration on grain yield, or "grain protein deviation", identified one genotype (Brawl CL Plus) that had 6.7 g kg −1 higher grain protein concentration than the average for all 20 genotypes. These results for a representative sample of a breeding population suggest that sufficient variation is available to improve NUE and grain protein deviation through breeding. Core Ideas We assessed variation available to improve N use efficiency and grain protein deviation through breeding. We determined variation for N use efficiency component traits in 20 breeding lines and cultivars. Nitrogen utilization efficiency contributed the most to variance for N use efficiency under moderate to high N. Nitrogen uptake efficiency contributed the most to variance for N use efficiency under N limiting conditions. Grain protein deviation varies among these genotypes; the highest was 6.7 g kg–1 above the mean.